Kontenmu Cerminan Dirimu: Bijak di Dunia Digital Bagi Gen-Z di Lingkungan Yayasan Louisa - Tony Soebijono; Martinus Sony Erstiawan; Lilis Binawati; Oktaviani Oktaviani (Jurnal Ragam Pengabdian, 2025)
The Current digital era posse great challenges for generation Z in using social media wisely, where the rise of hoaxes, misinformation and unetical digital behavior are serious problem. The low level of digital literacy among students, especially within the Louisa Foundaton, demands an educational intervention to create awareness that digital content is a reflection of one's identity and character. This service activity aims to improve digital literacy, evelop the ability to identify hoax information, foster awareness of digital ethics, develop critical thinking skills and form a positive and responsibble digital culture. The implementation method is carried out through three stages, namely preparation with group discussions and educational games and evaluation of activities. The acitvity was held for two days on June 6-7, 2025 at Wisma Kartini Pacet, Mojokerto invilving 50 participants form junior high to high school levels. The results of the activity showed the achievement of 100% participation target, a significant increase in understanding of digital literacy, and the formation of digital ethics awareness through the concept of self reflection content. This activity succeeded in achieving the goal of forming a digital generation that is smart, wise and responsible on interacting in cyberspace.